Spatial Blue Economy: Coastal Tourism Efficiency As an Application of Blue Economy in Jepara Region, Central Java, Indonesia - Irhamni, Muhammad Ricza; Astuti, Wulan Budi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
Coastal tourism is the oldest, most important, and rapidly growing segment of the tourism industry, but it is also a fragile and seasonal sector. The blue economy is significant in achieving sustainability and resilience to face challenges. During COVID-19 the tourism sector suffered a loss of 75% in 2020, recovery efforts continue to be carried out, but the lack of research in Indonesia, a country that is geographically majority oceanic, highlights a significant research gap. Using a quantitative method approach of efficiency analysis with data envelopment analysis (DEA), it focused on 12 centers of the central decision-making unit of the Jepara, Central Java tourism center to test the hypothesis. The results show that most coastal tourism is efficient and can continue its tourism management activities. The advice can make innovations to increase the number of tourists who visit locally and abroad. However, there are four inefficient tourism centers, namely Jepara Ourland Park, Blebak Beach, Mandalika Island, and Panjang Island. The government and investors are advised to focus on these inefficient tourism centers, by focusing on the distribution of the use of areas and coastlines, reviewing the investments given, and improving accommodation facilitation to increase tourist interest.